2010
DOI: 10.1002/elsc.200900107
|View full text |Cite
|
Sign up to set email alerts
|

Stirring and biomass starter influences the anaerobic digestion of different substrates for biogas production

Abstract: Here, we present the results of lab‐scale experiments conducted in a batch mode to determine the biogas yield of lipid‐rich waste and corn silage under the effect of stirring. Further semi‐continuous experiments were carried out for the lipid‐rich waste with/without stirring. Additionally, it was analyzed how the starter used for the batch experiment influences the digestion process. The results showed a significant stirring effect on the anaerobic digestion only when seed sludge from a biogas plant was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…It is probable that the increased concentrations of VFA in the methanogenic reactors were mainly caused by higher VFA concentrations in the fed substrate combined with an insufficient distribution of the substrate due to the stirring disturbances. Rojas et al [33] revealed a decreasing performance of the biogas process in a reactor without stirring and related it to the insufficient contact between substrate and microorganisms. After restart of the agitator in month 5, the VFA concentrations in the two methanogenic reactors remained on a low level although the VFA concentrations in the hydrolytic stage increased again to more than 24,000 mg L −1…”
Section: R1 R2mentioning
confidence: 99%
“…It is probable that the increased concentrations of VFA in the methanogenic reactors were mainly caused by higher VFA concentrations in the fed substrate combined with an insufficient distribution of the substrate due to the stirring disturbances. Rojas et al [33] revealed a decreasing performance of the biogas process in a reactor without stirring and related it to the insufficient contact between substrate and microorganisms. After restart of the agitator in month 5, the VFA concentrations in the two methanogenic reactors remained on a low level although the VFA concentrations in the hydrolytic stage increased again to more than 24,000 mg L −1…”
Section: R1 R2mentioning
confidence: 99%
“…An appropriate agitation technology is essential since stirring has a crucial influence on the microbial community structure and the SBY. Thus, it has been highlighted by previous authors a SBY reduction between 30 % to 40 % when the digestate is unmixed (Rusin et al, 2017;Rojas et al, 2010).…”
Section: Ad Testsmentioning
confidence: 79%
“…The structure and activity of the microbial community involved in fermenta-tion often depends on the original inoculum source and starter biomass, as well as the operational and environmental conditions [19] [20] [21] [22]. Bacterial communities in biogas plants adapt to the substrates fed [23].…”
Section: Impact Of Inoculum Source On Biogas Productionmentioning
confidence: 99%
“…Such contradictions could possibly be due to the different nature and microbial composition of the inoculum. Numerous studies show that the microbial communities and their behavior in biogas reactors are controlled mainly by the starter inocula [20] [24] [37] [38]. Due to the importance of starter inoculum on the system, using silage as a primary substrate may have varying results in biogas production, as this is dependent whether the microbial community is adapted to lactic acid or not.…”
Section: Biogas Production With Fresh Maize and Maize Silage In Batchmentioning
confidence: 99%